PELANGGARAN HAK CIPTA SINEMATOGRAFI DI INDONESIA: KAJIAN HUKUM PERSPEKTIF BERN CONVENTION DAN UNDANG-UNDANG HAK CIPTA - Regent; Revlina Salsabila Roselvia; M. Rahmat Hidayat; Hari Sutra Disemadi (Universitas Muhammadiyah Malang, 2021)
Copyright is a protection provided to people in the country of Indonesia as a form of appreciation for works that are made or produced in the form of visual, audiovisual, and other things and examples of these intellectual property rights such as songs, films, works of art in the form of paintings and many other things. The function of copyright itself is to protect these works from individuals who want to plagiarize or imitate these copyrighted works so that other people are encouraged to generate ideas and works for the Indonesian nation. And this is protected by Indonesian Copyright Law and as we know Copyright has various types and one of them is the cinematography which is regulated in Article 40 Letter m Copyright Law, an example of cinematography. these are like commercials, cartoons, and documentaries. The exclusive rights owned by the creator in Article 9 Copyright Law and the regulation of sanctions related to the perpetrator who records and distributes the recording or copyright infringement that he has committed are regulated in Electronic Information and Transaction Law and this research compare the Copyright of Indonesian law with the Bern Convention where in this convention there is the Droit Moral or the right of the creator to claim his creation and raise objections against acts that intend to change and reduce. The development of technology and the internet makes it easier for many things to become practical but there are increasing problems that arise in the field of Copyright in the field of cinematography such as imitation. Piracy or imitation is an act committed by irresponsible persons who want to profit from the work of another person without their permission or knowledge